Interpretación constitucional en conflictos de derechos, libertad de culto frente al derecho a la educación. - Vega Cornejo, Josselyn Daniela (2025)
The present work addresses the interaction and conflicts between freedom of religion and the right to education within the framework of Ecuadorian law, focusing on the analysis of Constitutional Court Ruling 112-20-JP/22 and its consolidated cases. It examines the recognition of both rights as fundamental under the Constitution of the Republic, exploring their scope, limitations, and the need for reconciliation under the principle of proportionality. The research identifies that certain religious practices may interfere with academic obligations, creating tensions with equal and universal access to education. Through an analysis of the ruling, the criteria used by the Court to resolve such conflicts are examined, highlighting the importance of reasonable accommodations by educational institutions without compromising the essence of academic activities or imposing disproportionate burdens. With a qualitative and descriptive approach, this study employs inductive-deductive, analytical-synthetic, bibliographic-documentary, and hermeneutic-legal methods to analyze constitutional regulations, international standards, and specific cases. The findings aim to demonstrate the complexity of balancing fundamental rights in a multicultural and multi-ethnic society, emphasizing the need for a clear and operational regulatory framework. This work proposes interpretive guidelines to strengthen the capacity of the State and institutions in managing these conflicts, fostering solutions that respect cultural and religious diversity while ensuring harmonious coexistence and non-discrimination.